Individual and work-related predictors of work outcomes related to sustainable employment among male shift and day workers - van de Ven, Hardy A.; Klein Hesselink, John; Bültmann, Ute; de Boer, Michiel R.; de Looze, Michiel P.; van der Klink, Jac JL; Brouwer, Sandra (Scandinavian Journal of Work, Environment & Health, 2014)
' ' OBJECTIVES ': 'The aim of this study was to examine which individual and work-related characteristics predict work outcomes related to sustainable employment among male shift and day workers. ' ' METHODS ': 'Between 1 September 2005 and 31 December 2009, data on individual and work-related characteristics of N=5640 employees of Tata Steel in the Netherlands were retrieved from the Occupational Health Service and company registers. Work outcomes related to sustainable employment were (i) temporarily being placed in less strenuous work, (ii) sickness absence ≥6 weeks, and (iii) leaving the organization. Cox proportional hazard analyses were performed for all outcome measures. ' ' RESULTS ': 'Similar predictors were found for shift and day workers although some differences were observed. For shift workers, high blood pressure and cardiovascular disease were important predictors for sickness absence. For day workers, insomnia was an important predictor of sickness absence ≥6 weeks. ' ' CONCLUSIONS ': 'Similar predictors in magnitude and direction were found for work outcomes related to sustainable employment among shift and day workers. Interventions aimed at enhancing sustainable employability should focus on individual and work-related characteristics.
Keywords: ageing; day work; day worker; individual predictor; men; occupational health; personnel turnover; shift work; shift worker; sustainable employment; work outcome; work schedule tolerance; work-related predictor